The Students’ Perception of Cooperative Learning with Think-Pair-Share Strategy in Teaching English Speaking - Akbarjono, Ali; Prandika Putra, Pebri; Nur Khasanah, Uswatun (Yayasan Darussalam Bengkulu, 2021)
This study aims to determine students’ perceptions of Cooperative Learning with Think-Pair-Share strategy in teaching English speaking. The method used in this study is a descriptive quantitative study. The sample consisted of the second-grade students in MTs Al-Qur’an Harsallkum from classes E and F consisting of 42 students. The census sampling technique was used in this study. The data collection technique used a questionnaire, namely a closed questionnaire that distribute to the respondents. The result of this study shows that the students were interested in learning English speaking by using small group work of Think-Pair-Share strategy type of Cooperative learning, it shows off the result of this study indicates that this strategy can increase their pronunciation, grammar, vocabulary, fluency in speaking English, and their comprehension of English in general students have positive perceptions about the use of Cooperative Learning with the Think-Pair-Share strategy in teaching English speaking with the total mean score was 96.38..